The Influence of Self-Capacity Enhancement, Personality, and Managerial Competence of Madrasah Principals on the Effectiveness of State Islamic Senior High Schools in the Riau Islands Province - Safiyah Riyantini; Kasful Anwar; Abdul Halim (Maneggio, 2026)
This study aims to examine and analyze the effects of Self-Capacity Enhancement, Personality, and Managerial Competence of Madrasah Principals on the Effectiveness of State Islamic Senior High Schools (Madrasah Aliyah Negeri) in the Riau Islands Province, both directly and indirectly through Managerial Competence as a mediating variable. This study employed a quantitative approach using a survey method. The respondents consisted of 207 teaching and educational staff from three State Islamic Senior High Schools in the Riau Islands Province. Data were collected using questionnaires and analyzed using path analysis. The results of the study indicate that: (1) Self-Capacity Enhancement (X₁) has a positive and significant effect on the Managerial Competence of Madrasah Principals (X₃), with a path coefficient of 0.379 and a significance value of 0.000; (2) Personality (X₂) has a positive and significant effect on Managerial Competence (X₃), with a path coefficient of 0.419 and a significance value of 0.000; (3) Self-Capacity Enhancement (X₁) and Personality (X₂) simultaneously have a significant effect on Managerial Competence (X₃), with an R² value of 0.507, indicating that 50.7% of the variance in Managerial Competence is explained by these two variables; (4) Self-Capacity Enhancement (X₁) has a positive and significant effect on Madrasah Effectiveness (X₄), with a path coefficient of 0.266 and a significance value of 0.000; (5) Personality (X₂) has a positive and significant effect on Madrasah Effectiveness (X₄), with a path coefficient of 0.150 and a significance value of 0.008; (6) Managerial Competence (X₃) has a positive and significant effect on Madrasah Effectiveness (X₄), with a path coefficient of 0.509 and a significance value of 0.000; (7) Self-Capacity Enhancement, Personality, and Managerial Competence simultaneously have a significant effect on Madrasah Effectiveness, with an R² value of 0.667, indicating that 66.7% of the variance in Madrasah Effectiveness is explained by these three variables; (8) Managerial Competence mediates the effect of Self-Capacity Enhancement on Madrasah Effectiveness, with an indirect effect of 0.193; and (9) Managerial Competence mediates the effect of Personality on Madrasah Effectiveness, with an indirect effect of 0.213. The implications of the study indicate that the Managerial Competence of Madrasah Principals is the variable with the strongest direct effect on Madrasah Effectiveness, with a path coefficient of 0.509. Furthermore, Managerial Competence serves as an important mechanism linking the Self-Capacity Enhancement and Personality of Madrasah Principals to Madrasah Effectiveness. Therefore, continuous efforts to develop self-capacity, strengthen personality, and enhance the managerial competence of Madrasah Principals are essential as strategies for improving the effectiveness of State Islamic Senior High Schools in the Riau Islands Province.